Game Theory and Cold War Rationality: A Review Essay - Weintraub, E. Roy (Journal of Economic Literature, 2017)
This essay reviews new histories of the role of game theory and rational decision making in shaping the social sciences, economics among them, in the postwar period. The recent books The World the Game Theorists Made by Paul Erickson and How Reason Almost Lost Its Mind: The Strange Career of Cold War Rationality by Paul Erickson, Judy Klein, Lorraine Daston, Rebecca Lemov, Thomas Sturm, and Michael Gordin raise a number of complex historical questions about the interconnections among game theory, utility theory, decision theory, optimization theory, information theory, and theories of rational choice. Moreover, the contingencies of time, place, and person call into question the usefulness of economists' linear narratives about the autonomous and progressive development of modern economics. The essay finally reflects on the challenges that these issues present for historians of recent economics. (JEL B23, C70, D74, N42)